Destructive Osteonecrosis of the Femoral Head After a Single Intra-Articular Corticosteroid Injection: A Report of Two Cases. (2020) - Ahmed, Abdulaziz F.; Hammad, Mohammed; Salameh, Motasem; Ahmed, Ghalib O.
Highlights: Accelerated femoral head osteonecrosis after a single dose intra-articular steroid injection is rare with few cases reported in the literature. Two patients developed rapid femoral head destruction at 14 and 11 weeks following a single intra-articular steroid injection, respectively. Cases of accelerated femoral head osteonecrosis with subsequent resorption can be treated successfully with total hip arthroplasty. Abstract: Introduction: Accelerated femoral head avascular necrosis after a single dose intra-articular steroid injection is a rare pathology. Few cases were reported in the literature. Most cases were managed with total hip arthroplasty. Case presentation: In this study, we report two rare cases of destructive osteonecrosis of the femoral head. Both patients presented with hip osteoarthritis that failed nonoperative measures. A single intra-articular corticosteroid injection was administered for each patient. Both patients had femoral head destruction and significant resorption at 14 and 11 weeks, respectively. Septic arthritis was ruled out by blood tests and joint aspiration. Total hip arthroplasty (THA) was undertaken and histology reports confirmed the osteonecrosis. The postoperative follow-up was uneventful with satisfactory hip function. Discussion and conclusion: Destructive osteonecrosis of the femoral head is a rare catastrophic potential complication of intra-articular corticosteroid injection. Hence, physicians must consider this complication when counseling patients before an intra-articular corticosteroid hip injection.